"A duty, an opportunity and a pleasure": connecting archives and public history. Issue 1 (2nd January 2021) - Haunton, Melinda; Salzedo, Georgie
ABSTRACT: This article explores the intersection of public history and archives, with particular reference to the practice of promoting broad participation in interpreting the historical past. Key concepts in public history such as democratising history, power dynamics, authenticity and the role of audiences in history-making are examined in dialogue with analogous archival concepts and activities. The extent to which UK archives are sites of public history is tested, providing evidence of the breadth of activity falling within a definition of public history and thereby demonstrating the value of engagement between these parallel disciplines. The article closes with suggestions for developing an ethics of public history within archives, informed by the theory and practice of both disciplines but with an essential focus on the specificity of the public history context of archives. The authors do not attempt to resolve areas of tension between the disciplines, but argue for a constructive relationship which recognises what public history has to teach archives and what in turn archives can bring to debates on sharing the past with wider audiences.